Pengaruh Kualitas Pelayanan, Harga Dan Promosi Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan - Sri Rahayu; Darman Syafe’i (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
The purpose of this research is to determine the influence of service quality, price and promotion on loyalty through cotumer satisfaction at Rocket Chicken Baturaja. The type of this research is Explanatory Research with data used in this study is primary data obtained using questionnaire and library research. Analysis of data using simple linear regression and multiple regression test with SPSS 26. While hypothesis testing using the t test, f test, correlation coefficient, and the coefficient of determination. Based on the analysis it can be concluded that there is a positive and significant influence between service quality to satisfaction, positive and significant influence between price to satisfaction, positive and significant influence between promotion to satisfaction, positive and significant influence between service quality, price and promotion to satisfaction between service quality to loyalty, positive and significat influence between price to loyalty, positive and significant influence between promotion to loyalty, there is positive and significant influence between service quality to loyalty, there is positive and significant influence between quality of the service, price and promotion to loyalty.